Validity Analysis of Guided Inquiry-based E-Module for Learning Hydrostatic Pressure - Siti Muslikatin; Bowo Sugiharto; Meti Indrowati (Postgraduate, University of Mataram, 2025)
This study aims to analyze the level of validity of the guided inquiry-based e-module on the material of liquid pressure as a teaching material that supports the active involvement of students in the learning process. The research method used is the research and development method (R&D) with a development model that refers to the 4D model (Define, Design, Develop, and Disseminate), limited to the development stage. The validity assessment instrument is ini the form of a validation sheet filled out by four experts, consisting of material experts, media experts, and learning experts. The aspects assessed include the appropriateness of the content, language, presentation and graphics. The validation results show that the developed e-module obtained an average score of 91% from media experts, 89% from material experts, 94% from language experts, and 92% from learning experts. Based on the research results of media experts material experts, and learning experts, it can be concluded that the guided inquiry-based e-module with an average rating of 92% is in the “very valid” category, making it suitable for use as a teaching material in science learning, especially on the topic of liquid pressure. These findings indicate that the guided inquiry-based e-module can be an innovative in improving the quality of science learning in junior high schools.